Los manglares de Colombia y la recuperación de sus áreas degradadas: revisión bibliográfica y nuevas experiencias - Álvarez-León, Ricardo (Instituto de Ecología, A.C., 2016)
A summary is given of the actual grade conditions and silvicultural experiences in the Colombian coast, with the species (Avicennia germinans, Conocarpus erectus, Laguncularia racemosa, Pelliciera rhizophorae y Rhizophora mangle) at the Caribbean coast; and the species (A. germinans, P. rhizophorae, R. spp.), at the Pacific Ocean coast. Due to disemination mechanism, main information belongs to red mangrove tree (R. mangle). It was also found that C. erectus as mangrove trees it is highly used in urban ornamentation scenery and landscape architecture, and A. germinans is essential in successional dynamics of salty soils and arid sea shores. Complementary knowledge of L. racemosa, M. oleifera and P. rhizophorae, as well as of the governmental protection measures, will contribute to the proper and sustainable management of these valuable mangrove ecosystems.